2017
DOI: 10.1016/j.ydbio.2017.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Netrin1 establishes multiple boundaries for axon growth in the developing spinal cord

Abstract: The canonical model for netrin1 function proposed that it acted as a long-range chemotropic axon guidance cue. In the developing spinal cord, floor-plate (FP)-derived netrin1 was thought to act as a diffusible attractant to draw commissural axons to the ventral midline. However, our recent studies have shown that netrin1 is dispensable in the FP for axon guidance. We have rather found that netrin1 acts locally: netrin1 is produced by neural progenitor cells (NPCs) in the ventricular zone (VZ), and deposited on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 48 publications
4
40
0
Order By: Relevance
“…However, the number of ROBO3 + neurons was lower than we anticipated in the BMP4-directed hEBs compared with the RA control. Mouse Robo3 is present at high levels on commissural neurons and their axons throughout the dorsal and intermediate spinal cord ( Sabatier et al., 2004 , Varadarajan and Butler, 2017 , Varadarajan et al., 2017 ). However, monkey Robo3 is primarily present on intermediate spinal neurons, and that the pioneering commissural axons appear to stem from this intermediate population ( Figure 6 D′).…”
Section: Discussionmentioning
confidence: 99%
“…However, the number of ROBO3 + neurons was lower than we anticipated in the BMP4-directed hEBs compared with the RA control. Mouse Robo3 is present at high levels on commissural neurons and their axons throughout the dorsal and intermediate spinal cord ( Sabatier et al., 2004 , Varadarajan and Butler, 2017 , Varadarajan et al., 2017 ). However, monkey Robo3 is primarily present on intermediate spinal neurons, and that the pioneering commissural axons appear to stem from this intermediate population ( Figure 6 D′).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in the vertebrate spinal cord have shown that expression of Netrin-1 in the floorplate is not required for ventral commissural axon ventral guidance, (Dominici et al 2017;Varadarajan and Butler 2017;Yamauchi et al 2017). Rather, expression in ventricular cells is important, possibly in a contact-mediated haptotactic event.…”
Section: Unc-33/crmp Regulates F-actin Polarity and Mt + End Accumulamentioning
confidence: 99%
“…However, recent reports have revised this model by demonstrating that Ntn1 produced by neural progenitors in the ventral ventricular zone of hindbrain and spinal cord neuroepithelium are essential for commissural axon extension toward the ventral midline in embryonic mice (Dominici et al., ; Varadarajan, et al., ; Yamauchi et al., ). These reports propose that, in mice, commissural axons are directed via Dcc‐dependent haptotaxis toward the ventral midline by Ntn1 produced and deposited at the pial surface of the hindbrain and spinal cord, not via a diffusible gradient of Ntn1 emanating from the floor plate (Dominici et al., ; Varadarajan & Butler, ; Varadarajan et al., ; Yamauchi et al., ). Therefore, regardless of how Ntn1 is presented to axons, it is clear that it functions to direct Dcc‐expressing commissural axons toward the ventral midline of the hindbrain and spinal cord during development.…”
Section: Biological Significancementioning
confidence: 99%